How these three schools in Indonesia could exceed the international average score in TIMSS 2015? - Fatmawati, Fasiha; Retnawati, Heri (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2018)
The achievement of students' mathematics learning is strongly influenced by how the learning process takes place in the classroom. But, that is not the only factor that could affect learning achievement. This research aimed to describe the advantages of learning in three schools in Indonesia with highest score in TIMSS 2015 which exceed international standard score. Participants in this case study research were teachers and students from the three elementary schools, that are SD N Gunungsaren, SD N Kentungan, and SD N Semanu III in Yogyakarta Province, Indonesia. Data triangulation had been conducted to test the validity of data collected by observation, in-depth interviews, and documentation. From the result, it can be concluded that the process of mathematics learning in the three schools implemented by involving students actively in learning activities. Each school had advantage that support the implementation of learning activities. SD N Semanu III supported by the completeness of the facilities in schools in the form of projectors that teachers use well in learning. The success of student learning in SD N Kentungan supported by parents' involvement which providing support and facilitate children's learning. Meanwhile, the success of learning in SD N Gunungsaren supported by teacher creativity factors developed through teacher training activities that applied in classroom.